Toward the processing speed theory of activities of daily living in healthy aging: normative data of the Functional Activities Questionnaire - Bezdicek, Ondrej; Stepankova, Hana; Martinec Novakova, Lenka; Kopecek, Miloslav (Aging clinical and experimental research, 2016)
BACKGROUND: The aim of this study was to describe an instrumental activities of daily living (IADL) measure: Functional Activities Questionnaire (FAQ), which is often used in clinical settings as a self- or informant-based measure of IADL. However, the FAQ's relationship with age or education in healthy aging has not been investigated. METHODS: FAQ and a neuropsychological battery were administered to old and very old Czech adults (n = 540). Participants met strict inclusion criteria for the absence of any active or past neurodegenerative disorders. RESULTS: FAQ is significantly dependent on age and education, but not gender. Younger subjects and those with higher education have the lowest scores in the FAQ and show a higher degree of functional independence. FAQ moderately correlates with speed of processing, visual-perceptual and executive functions measures (Trail Making Tests, Stroop Test) and depressive symptoms, but not with episodic memory (WMS-III logical memory). We present normative percentile values for different age groups from 60 to 96 years of age. CONCLUSIONS: The present study shows conclusively that IADL measures, such as FAQ, should not be used without appropriate normative data, especially in very old adults. Thus, it has the ability to differentiate functional dependence due to age-related decline from neurodegenerative disease.
Keywords: Male; Aging; Psychomotor Performance; psychomotorický výkon; Česká republika; Normative data; Executive Function; Age Factors; Aged; činnosti denního života; exekutivní funkce; senioři; deprese; mužské pohlaví; Memory, Episodic; referenční hodnoty; Motor Skills; Questionnaire; průzkumy a dotazníky; stupeň vzdělání; Neuropsychological Tests; Czech Republic; Reference Values; senioři nad 80 let; lidé; Activities of daily living; ženské pohlaví; Educational Status; Humans; stárnutí; věkové faktory; Aged, 80 and over; Instrumental activities of daily living; Activities of Daily Living; Normal aging; neuropsychologické testy; motorické dovednosti; Female; Surveys and Questionnaires; Depression; lidé středního věku; epizodická paměť; Visual Perception; Middle Aged; zraková percepce